Psychopathological and psychophysiological sequelae of childhood abuse in women without mental disorders - Rausch, Sophie (2019)
Experiences of childhood abuse may have detrimental effects on the psychopathological and psychophysiological level. Evidence from previous studies mainly supports the notion that CA-exposed individuals show higher psychopathological impairment, such as intrusive experiences, dissociation, impaired general functioning, as well as reduced satisfaction with QoL and sexuality, as compared to individuals who have not been exposed to CA. On a psychophysiological level, this impairment is reflected by elevated HR and reduced HRV levels. Additionally, altered pain sensitivity has been associated with a history of CA. As a major limitation, the majority of these studies did not assess or control for effects of mental disorders (i.e., PTSD), preventing from disentangling effects of trauma and a PTSD diagnosis. Another branch of research has explicitly assessed these variables in individuals with PTSD related to CA and other kind of PTE and has found comparable results in the respective variables. However, up to this point, there is a research gap of studies on CA-exposed individuals both with and without PTSD that may disentangle the effects of the mere exposure to CA per se against the effects of a consequential PTSD diagnosis. The aim of this dissertation was to examine a broad range of relevant psychopathological and psychophysiological sequelae of childhood abuse in women without mental disorders in order to disentangle the effects of trauma and psychopathology. For this purpose, two studies were conducted in order to focus on relevant psychopathological and psychophysiological aspects that are known to be impaired after experiencing CA and in patients with PTSD related to CA. These relevant aspects encompassed a broad range of general and PTSD-specific psychopathology, general functioning, quality of life, and satisfaction with sexuality. Additionally, stress responsiveness was examined at the subjective and psychophysiological level in response to experimentally induced stress. Furthermore, pain sensitivity at baseline as well as in response to stress were examined. These features were examined in HTEW as compared to HC women without a history of CA and female patients with PTSD related to experiences of CA. In study I, HTEW showed a high level of functioning and a very low level of pathological impairment that was comparable to the level of healthy controls. The results of study I in this dissertation suggest that PTE exposure per se does not necessarily have to go along with the development of psychopathology or impaired quality of life, sexuality, self-esteem, or guilt cognitions. Results of the present study rather suggest an association of PTSD and impairment in the reported variables. In the second study, the most distinct and clinically meaningful effects between HTEW and PTSD-patients were observed concerning subjective stress parameters. With regard to subjective ratings of stress and dissociation, HTEW were clearly different from PTSD-patients while resembling the group of HC. With respect to the psychophysiological parameters (HR and HRV) and pain sensitivity, the picture was less clear: Although HTEW differed significantly from PTSD-patients with respect to HR and HRV, differences were not as pronounced as for the subjective ratings. With respect to pain sensitivity in response to experimentally induced stress, comparisons of HTEW and PTSD-patients only approached significance. In comparison to HC, HTEW differed significantly for HR, HRV, and pain sensitivity. On a descriptive level, HR, HRV and pain sensitivity levels of HTEW were located in between levels of HC and of PTSD-patients. Results of the second study of this dissertation reveal that differences between HTEW and PTSD-patients in baseline stress levels as well as stress responses were most distinct in subjective as compared to psychophysiological readouts. This may imply that subjective stress rating and dissociation may be seen as diagnostic correlates of PTSD rather than being related to experiences of CA per se. Results of the objective stress indicators draw a less clear picture: Although HTEW differed significantly from PTSD-patients and HC with respect to HR and HRV, differences between HTEW and PTSD-patients were not as pronounced as for the subjective indicators of stress. Taken together, based on recent advances in this field as well as results of our own work, it is proposed that psychopathology in form of a PTSD diagnosis seems to contribute to more general psychopathology (i.e., intrusions and dissociation), impaired general functioning, reduced QoL and satisfaction with sexuality, impaired baseline stress levels as well as stress responsiveness on a subjective as well as psychophysiological level. However, results of study II also suggest that one cannot exclude an additional role of CA on psychophysiological stress responses as well as pain sensitivity as the data also indicates that a small proportion of altered stress response may relate to experiences of CA per se. The contribution of this dissertation is an increased knowledge on the sequelae of CA apart from developing PTSD. Improved knowledge on the sequelae of CA may help identifying novel diagnostic markers to detect individuals who are at risk of developing PTSD. An early detection of vulnerability to PTSD in turn would help prevent developing a full-blown PTSD, as preventive programs could be called into action at an earlier stage. Furthermore, the recognition of these mechanisms and sequelae can help improve treatment planning in terms of potential accompanying symptoms that are not entailed as diagnostic criteria of PTSD (i.e., reduced self-esteem, reduced satisfaction with QoL and sexuality). Furthermore, results of this dissertation suggest that good self-esteem, absence of guilt cognitions, as well as the process of disclosure seem to be important in withstanding adversities unscathed. With potentially important implications for treatment, these findings highlight the importance of routinely inquiring about CA as well as educating and training support-providers and society about sexual and physical assault. Training programs should encompass how to respond to disclosure of CA in more supportive ways. Furthermore, the implementation of prevention programs focused on developing and supporting the adolescent’s sense of being a good and worthy person should be encouraged.
Keywords: Hochschulschrift